Self-healing positive electrode material, secondary battery and preparation method
By covering the self-healing polymer film on the positive electrode material matrix, the problems of microcracks and damage during charging and discharging are solved, and the long life and efficient conductivity of the battery are achieved.
Patent Information
- Application Number
- CN202411754197.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
Existing positive electrode materials are prone to microcracks and damage during charging and discharging, resulting in attenuation of battery capacity and shortening of cycle life. Especially under high-rate charging and discharging and extreme working conditions, the failure of the cladding layer affects the electrochemical performance and safety of the battery.
The positive electrode material matrix is coated with a self-healing polymer film, which includes a polymer, a lithium salt and a conductive material, and is coated and cured by impregnation or coating to form a film layer with self-healing properties and excellent ionic conductivity.
Effectively repair microcracks and surface damage caused by charging and discharge, extend the battery life, improve cycle stability, and improve lithium ion conductivity and electronic conductivity.
Smart Images

Figure CN119560538A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a self-healing positive electrode material, a secondary battery and a preparation method thereof. Background Art
[0002] With the widespread use of electric vehicles and portable electronic devices, the demand for secondary batteries continues to grow, especially high energy density batteries. Positive electrode materials are prone to performance degradation during long-term charging and discharging, especially due to damage to the surface structure, which leads to battery capacity decay and shortened cycle life. To solve these problems, researchers have proposed a variety of methods, such as surface coating technology, to improve the cycle stability and safety of materials. Common coating materials include oxides, fluorides, conductive polymers, etc. These coating materials can prevent structural changes in positive electrode materials to a certain extent, reduce direct contact between electrolyte and positive electrode materials, and delay battery performance degradation.
[0003] However, in the existing technology, most coating materials cannot effectively solve the problem of microcracks and damage that occur during the battery charging and discharging process. Especially under high-rate charging and discharging and extreme working conditions, cracks and damage will lead to the failure of the coating layer, thereby affecting the electrochemical performance and safety of the battery. Therefore, how to provide long-term protection for the positive electrode material while ensuring that cracks and damage can be suppressed during the use of the battery is an important problem that needs to be solved in current battery technology.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present invention, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a self-healing positive electrode material, a secondary battery and a preparation method.
[0006] According to a first aspect of the present invention, a self-healing positive electrode material is provided, comprising a positive electrode material substrate and a self-healing polymer film coated on the surface of the positive electrode material substrate, wherein the material of the self-healing polymer film comprises a polymer, a lithium salt and a conductive material.
[0007] In an exemplary embodiment of the present invention, the polymer is selected from one or more of PEO, PEGDA, PU, PEO-PEGDA copolymer, PEGDA-PU copolymer, PEO-PU copolymer and PEO-PEGDA-PU copolymer; and / or, the lithium salt is selected from one or more of LiTFSI, LiFSI and LiPF6; and / or, one or more of the carbon nanotubes, graphene and carbon black.
[0008] In an exemplary embodiment of the present invention, the chemical formula of the positive electrode material matrix is Li 1+ a Ni x Co y Mn z A m O2, wherein -0.2≤a≤0.2, 0.7≤x≤1, 0<y≤0.2, 0≤z≤0.2, 0≤m≤0.05, x+y+z+m=1, and A is selected from at least one of Zr, Y, W, Ce, Mo, Ba, Ti, Mg, Ta, Sb, B, Sn, Sr, Al, F and Nb.
[0009] In an exemplary embodiment of the present invention, the mass of the self-healing polymer film does not exceed 2% of the total mass of the self-healing positive electrode material.
[0010] In an exemplary embodiment of the present invention, the thickness of the self-healing polymer film is 0.1-15 nm.
[0011] According to a second aspect of the present invention, there is provided a method for preparing a self-healing positive electrode material as described in any one of the above, comprising the following steps:
[0012] S1, obtaining the positive electrode material matrix;
[0013] S2, preparing a polymerization solution, wherein the polymerization solution contains the polymer, the lithium salt and the conductive material;
[0014] S3, coating the polymer solution on the surface of the cathode material substrate by dipping or coating, and then curing to obtain the self-healing cathode material.
[0015] In an exemplary embodiment of the present invention, the polymer is selected from PEO-PEGDA copolymer, PEGDA-PU copolymer, PEO-PU copolymer or PEO-PEGDA-PU copolymer, and in step S2, the step of preparing the polymerization solution includes: mixing the polymer precursor in an organic solution, adding the lithium salt and the conductive material, mixing to obtain a mixed solution, adding a photoinitiator to the mixed solution to obtain the polymerization solution, wherein the polymer precursor is selected from at least two of a PEO precursor, a PEGDA precursor and a PU precursor.
[0016] In an exemplary embodiment of the present invention, the step of preparing the mixed solution comprises: dissolving one of the polymer precursors in an organic solvent to obtain a first solution; mixing another one or two of the polymer precursors with an organic solvent to obtain a second solution; after mixing the first solution and the second solution, adding a solution containing the lithium salt, continuously stirring and mixing for 0.5 to 2 hours, adding the conductive material, and ultrasonically treating for 20 to 60 minutes to obtain the mixed solution.
[0017] In an exemplary embodiment of the present invention, in step S3, the curing step is: irradiating the positive electrode material substrate coated with the polymerization solution under ultraviolet light for 20 to 60 minutes, and then vacuum drying to obtain the self-healing positive electrode material; or, after drying the positive electrode material substrate coated with the polymerization solution, heating and curing it at 75 to 100° C. for 1 to 3 hours.
[0018] In an exemplary embodiment of the present invention, in the polymer solution, the mass of the lithium salt is 15-30% of the polymer, and the amount of the conductive material is 0.5-3% of the polymer.
[0019] According to a third aspect of the present invention, there is provided a secondary battery, comprising the self-healing cathode material as described in any one of the above, or the self-healing cathode material prepared by the preparation method as described in any one of the above.
[0020] The beneficial effects of the self-healing positive electrode material, secondary battery and preparation method of the embodiments of the present invention are:
[0021] In the embodiments of the present invention, a self-healing positive electrode material is prepared, and the surface of the positive electrode material is coated with a self-healing polymer film, which has excellent ionic conductivity and can repair microcracks and surface damage caused by charging and discharging during the use of the battery, thereby extending the service life of the battery and improving its cycle stability. In addition, by adding lithium salts (such as LiPF6, LiTFSI, etc.) to the polymer film for compounding, in addition to giving the film layer good self-healing properties, it also has efficient lithium ion conductivity. Furthermore, by adding conductive materials (such as graphene, carbon nanotubes, etc.), the ionic conductivity and electronic conductivity of the self-healing polymer film can be effectively improved.
[0022] The positive electrode material with a self-healing polymer film of the present invention has broad application prospects, especially in the field of high energy density lithium-ion batteries such as electric vehicles and energy storage systems. It can effectively improve the cycle life, damage resistance and high rate performance of the battery, so that the battery maintains excellent electrochemical properties during long-term use.
[0023] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 This is a SEM image of the positive electrode material provided in Example 3 of the present invention after 100 charge and discharge cycles.
[0026] Figure 2 This is a SEM image of the positive electrode material provided in Example 5 of the present invention after 100 charge and discharge cycles.
[0027] Figure 3 This is a SEM image of the positive electrode material provided in Comparative Example 1 of the present invention after 100 charge and discharge cycles. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the embodiments of the present disclosure clearer, the technical scheme in the embodiments of the present disclosure will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0029] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0030] The embodiment of the present invention provides a self-healing positive electrode material, comprising a positive electrode material substrate and a self-healing polymer film coated on the surface of the positive electrode material substrate. The material of the self-healing polymer film comprises a polymer, a lithium salt and a conductive material.
[0031] Specifically, the polymer is selected from one or more of PEO (polyethylene oxide), PEGDA (polyethylene glycol dimethacrylate), PU (polyurethane), PEO-PEGDA (polyethylene oxide-polyethylene glycol dimethacrylate) copolymer, PEGDA-PU (polyethylene glycol dimethacrylate-polyurethane) copolymer, PEO-PU (polyethylene oxide-polyurethane) copolymer and PEO-PEGDA-PU (polyethylene oxide-polyethylene glycol dimethacrylate-polyurethane) copolymer. Among them, PEO is a polymer with high ionic conductivity and can provide a good lithium ion conduction path. PEGDA has cross-linking properties and can be used in the film layer to improve the mechanical strength and self-healing ability of the polymer. PU has high elasticity and toughness, which can effectively enhance the performance of the material in crack repair.
[0032] More preferably, the polymer is selected from one or more of PEO-PEGDA copolymer, PEGDA-PU copolymer, PEO-PU copolymer and PEO-PEGDA-PU copolymer. The above copolymers can play a synergistic role by cross-linking each other, so that the polymer film has better crack resistance and conductivity. By introducing PEGDA with cross-linking ability into the copolymer, the self-healing property can be exerted when cracks occur, and the movement of the material segments is stimulated by heating or humidity, so that the cracked parts are re-contacted and cross-linked, thereby achieving self-healing. The introduction of PU provides flexibility and high elasticity, so that the polymer can relieve fracture and recover under crack stress.
[0033] For example, PEO-PEGDA copolymers can greatly improve the mechanical strength and durability of polymer films. PEO-PU copolymers can form a network structure with hard and soft segments when PU and PEO work together. The hard segment (urethane group of PU) can increase mechanical strength and durability, while the soft segment (PEO segment) provides sufficient flexibility and ionic conductivity. The copolymer can relieve stress when cracks appear, and the overall material can still maintain excellent electrochemical properties after self-healing. PEGDA-PU copolymers form good mechanical protection for materials through cross-linking between PEGDA and PU, which can greatly reduce the occurrence of cracks. PEO-PEGDA-PU copolymers cross-link PEO, PEGDA and PU. The addition of PEGDA or PU can adjust the cross-linking density of the polymer to form a continuous conductive network while ensuring mechanical strength. Not only has the conductivity of the film layer been effectively improved, but the mechanical strength and flexibility of the material have also been further enhanced, and the self-healing property is better.
[0034] Further, in the PEO-PEGDA copolymer, the mass ratio of PEO and PEGDA is 1:0.6-0.9, and more preferably, the mass ratio of PEO and PEGDA is 1:0.8. Further, in the PEO-PU copolymer, the mass ratio of PEO and PU is 1:0.6-0.9, and more preferably, the mass ratio of PEO and PU is 1:0.8. Further, in the PEO-PEGDA-PU copolymer, the amount ratio of PEO, PEGDA and PU is 1:0.3-0.5:0.3-0.5. By adjusting the content of the polymers of the above polymers, the film layer can be given better guidance and self-healing properties.
[0035] Furthermore, the lithium salt is selected from one or more of LiTFSI, LiFSI and LiPF6. The efficient transmission of lithium ions is greatly promoted by combining the lithium salt with the polymer membrane.
[0036] Furthermore, one or more of the carbon nanotubes, graphene and carbon black can provide additional electron conduction paths for the positive electrode material by further introducing conductive materials into the polymer film.
[0037] In an exemplary embodiment of the present invention, the chemical formula of the positive electrode material matrix is Li 1+ a Ni x Co y A z B m O2, wherein -0.5≤a≤0.5, 0.7≤x≤1, 0<y≤0.2, 0≤z≤0.2, 0≤m≤0.05, x+y+z+m=1, A is selected from at least one of Mn and Al, and B is selected from at least one of Zr, Y, W, Ce, Mo, Ba, Ti, Mg, Ta, Sb, B, Sn, Sr, Al, F and Nb. It is understood that the positive electrode material matrix can be prepared by existing technology and will not be described in detail here.
[0038] Furthermore, the mass of the self-healing polymer film does not exceed 2% of the total mass of the self-healing positive electrode material. The thickness of the self-healing polymer film is 0.1 to 15 nm. More preferably, the thickness of the self-healing polymer film is 0.5 to 3 nm. Specifically, during the preparation process, the thickness of the polymer film can be adjusted by adjusting the concentration of the polymerization solution.
[0039] This embodiment also provides a method for preparing the above-mentioned self-healing positive electrode material, comprising the following steps:
[0040] S1, obtaining the positive electrode material matrix;
[0041] S2, preparing a polymerization solution, wherein the polymerization solution contains the polymer, the lithium salt and the conductive material;
[0042] S3, coating the polymer solution on the surface of the cathode material substrate by dipping or coating, and then curing to obtain the self-healing cathode material.
[0043] Furthermore, when the polymer is selected from PEO-PEGDA copolymer, PEO-PU copolymer or PEO-PEGDA-PU copolymer, in step S2, the step of configuring the polymerization solution includes: mixing the polymer precursor in an organic solution, adding the lithium salt and the conductive material, mixing to obtain a mixed solution, adding a photoinitiator to the mixed solution to obtain the polymerization solution. Wherein, the polymer precursor is selected from at least two selected from PEO precursor, PEGDA precursor and PU precursor. Under the action of the photoinitiator, various polymer precursors undergo polymerization reaction to form copolymers. For example, PEO precursor and PEGDA precursor generate PEO-PEGDA copolymer through polymerization reaction. In this step, the lithium salt and the conductive material can be evenly dispersed in the polymer film by in-situ polymerization, which further improves the electrochemical properties of the material.
[0044] Furthermore, in this step, the organic solvent may be, for example, tetrahydrofuran, acetonitrile, methanol, etc. The photoinitiator may be, for example, 2-hydroxy-2-methyl-1-phenyl-1-propanone (Irgacure 1173), 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), phenacyltrimethylsilane (BMS), etc.
[0045] Furthermore, in this step, the step of mixing the solution may include: dissolving one of the polymer precursors in an organic solvent to obtain a first solution; mixing another one or two of the polymer precursors with an organic solvent to obtain a second solution; after mixing the first solution and the second solution, adding the solution containing the lithium salt, stirring and mixing for 0.5 to 2 hours, adding the conductive material, and ultrasonically treating for 20 to 60 minutes to obtain the mixed solution. In this method, by dissolving PEO and PEGDA / PU separately and then adding the lithium salt and the conductive material, the uniform distribution of the lithium salt in the polymer can be ensured, and a higher ionic conductivity is provided.
[0046] Furthermore, in step S3, when the polymer is selected from a copolymer, the curing step is: irradiating the positive electrode material substrate coated with the polymerization solution under ultraviolet light for 20 to 60 minutes, and then vacuum drying to obtain the self-healing positive electrode material; or, drying the positive electrode material substrate coated with the polymerization solution, and then heating and curing it at 75 to 100° C. for 1 to 3 hours.
[0047] Furthermore, in step S3, when the polymer is selected from one of PEO, PEGDA, and PU, the curing step is: drying the positive electrode material matrix coated with the polymer solution, and then heating and curing it at 75 to 100° C. for 1 to 3 hours.
[0048] Furthermore, in the polymerization solution, the mass of the lithium salt is 15-30% of the polymer, and the amount of the conductive material is 0.5-3% of the polymer.
[0049] An embodiment of the present invention also provides a secondary battery, comprising the self-healing positive electrode material described above, or a self-healing positive electrode material prepared according to the preparation method described above. It is understandable that the secondary battery can be prepared according to known methods in the prior art. The secondary battery can be, for example, a lithium ion battery or a sodium ion battery. When applied to a sodium ion battery, the positive electrode material matrix of the self-healing positive electrode material can be, for example, a layered oxide (such as NaxCoO2, NaxMnO2), a sodium transition metal phosphate (such as NaFePO4) or other materials suitable for sodium ion insertion and extraction reactions.
[0050] Example 1
[0051] This embodiment provides a self-healing positive electrode material, which is obtained by following the steps below:
[0052] (1) Nickel-cobalt-manganese ternary material (Ni:Co:Mn=90:6:4) is selected as the positive electrode material matrix, and the particle size of the matrix is about 13 μm.
[0053] (2) PEO (5 g) and LiTFSI were dissolved in tetrahydrofuran at a mass ratio of 1:0.2 to obtain a uniform solution. 0.05 g of carbon nanotubes (CNT) were added to the above solution and ultrasonically treated for 30 min to obtain a polymerization solution.
[0054] (3) The positive electrode material substrate is immersed in the above-mentioned polymerization solution and kept at room temperature for 1 hour to allow the polymer solution to completely coat the material surface. The concentration of the solution is adjusted to control the coating thickness to be 1 nm.
[0055] (4) The coated material was placed in an oven at 70°C for 6 hours and then further cured at 80°C for 2 hours to obtain a self-healing positive electrode material.
[0056] Example 2
[0057] This embodiment provides a self-healing positive electrode material, which is obtained by following the steps below:
[0058] (1) Select the same positive electrode material matrix as in Example 1;
[0059] (2) Dissolve 5g of PEO precursor and 3g of PEGDA precursor in 40mL of THF, mix and stir for 2h until a uniform solution is formed. Then add a lithium salt solution containing 1g of LiTFSI and continue stirring for 1h. Then add 0.05g of CNT, ultrasonically disperse for 30min, add 0.1g of photoinitiator, stir evenly, and obtain a polymerization solution.
[0060] (3) The positive electrode material substrate is immersed in the above-mentioned polymerization solution and kept at room temperature for 1 hour to allow the polymer solution to completely coat the material surface. The concentration of the solution is adjusted to control the coating thickness to be 1 nm.
[0061] (4) The coated material was placed under ultraviolet light for 30 minutes to allow PEO and PEGDA to undergo a cross-linking reaction and form a copolymer. The cured sample was treated under vacuum conditions at 80°C for 2 hours to remove the residual solvent, forming a uniform and stable polymer film layer, and obtaining a self-healing positive electrode material.
[0062] Example 3 (Examples 3 and 4 are repeated in the explanation, and Example 3 is adjusted to PEO-PU)
[0063] This embodiment provides a self-healing positive electrode material, which is different from that in Embodiment 2 in that:
[0064] In step (2), 5 g of PEO precursor and 3 g of PU precursor were dissolved in 40 mL of THF respectively, and then mixed and stirred for 2 h until a uniform solution was formed.
[0065] Example 4
[0066] This embodiment provides a self-healing positive electrode material, which is different from that in Embodiment 2 in that:
[0067] In step (2), 5 g of PEGDA precursor and 3 g of PU precursor were dissolved in 40 mL of THF respectively, and then mixed and stirred for 2 h until a uniform solution was formed.
[0068] Example 5
[0069] This embodiment provides a self-healing positive electrode material, which is different from that in Embodiment 2 in that:
[0070] In step (2), 5 g of PEO precursor was dissolved in 40 mL of THF, and 1.5 g of PEGDA precursor and 1.5 g of PU precursor were dissolved in 40 mL of THF, and then mixed and stirred for 2 h until a uniform solution was formed.
[0071] Comparative Example 1
[0072] This comparative example provides a positive electrode material, which is consistent with the positive electrode material matrix in Example 1.
[0073] Comparative Example 2
[0074] This comparative example provides a self-healing positive electrode material, which is different from Example 1 in that:
[0075] In step (2), PEO (5 g) and LiTFSI were dissolved in tetrahydrofuran at a mass ratio of 1:0.2 to obtain a uniform solution, which was then ultrasonically treated for 30 min to obtain a polymerization solution.
[0076] Comparative Example 3
[0077] This comparative example provides a self-healing positive electrode material, which is different from Example 1 in that:
[0078] In step (2), 5 g of PEO was dissolved in tetrahydrofuran, 0.05 g of CNT was added, and ultrasonic treatment was performed for 30 min to obtain a polymerization solution.
[0079] The self-healing positive electrode materials prepared in Examples 1 to 5 and the positive electrode materials prepared in Comparative Examples 1 to 3 were respectively used as samples. Each sample was mixed with superconducting carbon black SP and polyvinylidene fluoride PVDF in a mass ratio of 94:3:3, and the mixture was adjusted into slurry with N-methyl-pyrrolidone (NMP); the slurry was evenly coated on an aluminum foil current collector to obtain a positive electrode film. With lithium metal sheet as negative electrode, polypropylene microporous membrane as separator, 1mol / LiPF6 (solvent is a mixture of ethylene carbonate and dimethyl carbonate with a volume ratio of 1:1) as electrolyte, button cells were assembled in an Ar gas-protected glove box, and the electrical performance was tested by button charging. The test conditions were as follows: first charge and discharge test: charge to 4.3V at 0.1C rate, stand for 5 minutes, and discharge to 3.0V at 0.1C rate; normal temperature cycle 100 cycles test: at room temperature 25℃, charge to 4.3V at 0.5C rate, stand for 5 minutes, discharge to 3.0V at 0.5C rate, and cycle 100 cycles. The test results are shown in Table 1.
[0080] Table 1
[0081]
[0082]
[0083] It can be seen from Table 1 that the self-healing positive electrode material obtained in the embodiment of the present invention has a higher discharge capacity and exhibits good cycle stability.
[0084] like Figure 1 to Figure 3 The following are scanning electron microscope (SEM) images of Example 1, Example 5 and Comparative Example 1 after 100 cycles of charge and discharge. After 100 cycles of charge and discharge, the degree of particle breakage was observed by CP-SEM. Compared with Comparative Example 1 without coating, the embodiment of the present invention forms a self-healing polymer film on the surface of the positive electrode material, so that microcracks are effectively suppressed during the charge and discharge process, and the stability of the battery is effectively improved.
[0085] The above description is not all embodiments. The detailed description of the embodiments of the present disclosure is not intended to limit the scope of the present disclosure for protection, but merely represents selected embodiments of the present disclosure. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present disclosure.
Claims
1. A self-healing positive electrode material, characterized in that: The invention comprises a positive electrode material matrix and a self-healing polymer film coated on the surface of the positive electrode material matrix, wherein the material of the self-healing polymer film comprises a polymer, a lithium salt and a conductive material.
2. The self-healing positive electrode material according to claim 1, characterized in that: The polymer is selected from one or more of PEO, PEGDA, PU, PEO-PEGDA copolymer, PEGDA-PU copolymer, PEO-PU copolymer and PEO-PEGDA-PU copolymer; And / or, the lithium salt is selected from one or more of LiTFSI, LiFSI and LiPF6; And / or, the conductive material is selected from one or more of carbon nanotubes, graphene and carbon black.
3. The self-healing cathode material according to claim 1, characterized in that: The chemical formula of the positive electrode material matrix is Li 1+a Ni x Co y Mn z A m O2, wherein -0.2≤a≤0.2, 0.7≤x≤1, 0<y≤0.2, 0≤z≤0.2, 0≤m≤0.05, x+y+z+m=1, and A is selected from at least one of Zr, Y, W, Ce, Mo, Ba, Ti, Mg, Ta, Sb, B, Sn, Sr, Al, F and Nb.
4. The self-healing positive electrode material according to claim 1, characterized in that: The mass of the self-healing polymer film does not exceed 2% of the total mass of the self-healing positive electrode material; and / or the thickness of the self-healing polymer film is 0.1 to 15 nm.
5. A method for preparing a self-healing positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, obtaining the positive electrode material matrix; S2, preparing a polymerization solution, wherein the polymerization solution contains the polymer, the lithium salt and the conductive material; S3, coating the polymer solution on the surface of the cathode material substrate by dipping or coating, and then curing to obtain the self-healing cathode material.
6. The method for preparing the self-healing positive electrode material according to claim 5, characterized in that: The polymer is selected from PEO-PEGDA copolymer, PEGDA-PU copolymer, PEO-PU copolymer or PEO-PEGDA-PU copolymer. In step S2, the step of preparing the polymerization solution includes: mixing the polymer precursor in an organic solution, adding the lithium salt and the conductive material, mixing to obtain a mixed solution, adding a photoinitiator to the mixed solution to obtain the polymerization solution, wherein the polymer precursor is selected from at least two of a PEO precursor, a PEGDA precursor and a PU precursor.
7. The method for preparing a self-healing positive electrode material according to claim 6, characterized in that: The steps of preparing the mixed solution include: dissolving one of the polymer precursors in an organic solvent to obtain a first solution; mixing another one or two of the polymer precursors with an organic solvent to obtain a second solution; after mixing the first solution and the second solution, adding a solution containing the lithium salt, continuously stirring and mixing for 0.5 to 2 hours, adding the conductive material, and ultrasonically treating for 20 to 60 minutes to obtain the mixed solution.
8. The method for preparing the self-healing positive electrode material according to claim 5, characterized in that: In step S3, the curing step is: irradiating the positive electrode material substrate coated with the polymerization solution under ultraviolet light for 20 to 60 minutes, and then vacuum drying to obtain the self-healing positive electrode material; or, after drying the positive electrode material substrate coated with the polymerization solution, heating and curing at 75 to 100° C. for 1 to 3 hours.
9. The method for preparing a self-healing positive electrode material according to claim 5, characterized in that: In the polymer solution, the mass of the lithium salt is 15-30% of the polymer, and the amount of the conductive material is 0.5-3% of the polymer.
10. A secondary battery, characterized in that: The invention comprises the self-healing positive electrode material according to any one of claims 1 to 4, or the self-healing positive electrode material prepared by the preparation method according to any one of claims 5 to 9.